Entrepreneurship In The Digital Era: A Systematic Literature Review - Rahman, Izzatul Luthfiah; Dias Intan Sholatiah; Sari Ayu Imaniah; Irma Suryandari; Andy Prasetyo Wati; Fulgentius Danardana Murwani; Ludi Wishnu Wardana (International Journal of Technology and Education Research, 2025)
This research aims to identify, analyze, and synthesize relevant literature on entrepreneurship in the digital era through a Systematic Literature Review (SLR) approach. Digitalization has significantly changed the entrepreneurial paradigm, driving the emergence of new business models, expanding market access, and requiring entrepreneurs to have adequate technological, cognitive, and social skills. This review analyzed 11 selected scholarly articles from reputable databases such as Scopus, Emerald, Sciencedirect, and SpringerLink, published between 2020 and 2025. The review shows that digital entrepreneurship is strongly influenced by technology adoption, organizational readiness, and individual factors such as digital efficacy. The research also uncovered gaps in the literature, such as the lack of studies in developing country contexts, the role of human factors in SMEs' digital transformation, as well as the need for integration of psychosocial factors. This study offers a new conceptual framework and model to support the development of sustainable and adaptive digital entrepreneurship